(untitled) (Comparative & International Education Series, 2021)
This chapter argues that responses from Black students about study abroad participation are narrowly analyzed and misinterpreted using deficit-based presumptions, resulting in ineffective attempts to increase their participation. To elucidate key misalignments between responses and analysis, it examines claims that lack of funds and interest are the major barriers to participation, unpacks these claims, identifies deficit-based presumptions, and reexamines Black student responses to provide a deeper analysis. Based on this analysis, surveys were conducted with Historical Black Colleges and Universities (HBCU) students about their interest in Study Abroad Programs (SAP) in Africa. Findings from these surveys are used to add previously missing student voices from the body of research and to make suggestions for institutions looking to increase Black student study abroad participation.